Hypertensive disorders of pregnancy and its outcome in a tertiary care hospital (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Hypertensive disorders of pregnancy seem to be one of the major causes of maternal morbidity and mortality leading to 10-15% of maternal deaths specially in developing world. Pregnancies complicated with hypertensive disorders are associated with increased risk of adverse foetal, neonatal and maternal outcome including preterm birth, Intrauterine Growth Retardation (IUGR) and perinatal death. Objectives: The objective of the study was to determine the hypertensive disorders and its outcome. Methods: The observational study was conducted on 63 randomly selected patients admitted in the inpatients department of Gynaecology and Obstetrics at the Institute of Child and Mother Health, Matuail, Dhaka from 1st November 2010 to 30th January 2011. Results: Among the study subjects 46% were within 19-25 years of age. 79.4% had preeclampsia, 14.3% had eclampsia and 6.3% were found to be as gestational hypertension. Among the study patients 50.8% were of single parity and 61.9% had no antenatal checkups, 25.4% were delivered before 37 completed weeks of pregnancy and 50.8% were delivered by Caesarean section. Regarding pregnancy outcome there was one case of still birth. Intra-uterine growth retardation had 33.3% and 44.4% had low birth weight (